2021
DOI: 10.1002/clen.202000440
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Washing of Wet and Dry Crude Oil‐Contaminated Soil

Abstract: Two types of artificial oil‐contaminated soils (OCS) are prepared upon mixing sandy soil with water and crude oil in different proportion. OCS‐I represents the contaminated dry soil and OCS‐II the contaminated wet soil. Soil and crude oil are characterized through infrared spectroscopy and zeta potential analysis, and the OCS microstructure model has been discussed. It is speculated that the polarity petroleum components (e.g., non‐hydrocarbons) are higher in the oil layer of the neighboring soils, forming a “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…These observations are in agreement with the report of Qi, B. et al (2021) on the effect of dry and wet soil on oil removal, where they found that the dry soil (even for sandy soil, which is relatively easy to wash) is selective and the adherence of the strong polarity compounds presented in the crude oil exhibits difficult mobility (Qi et al 2021).…”
Section: Free Water Washing Testssupporting
confidence: 92%
“…These observations are in agreement with the report of Qi, B. et al (2021) on the effect of dry and wet soil on oil removal, where they found that the dry soil (even for sandy soil, which is relatively easy to wash) is selective and the adherence of the strong polarity compounds presented in the crude oil exhibits difficult mobility (Qi et al 2021).…”
Section: Free Water Washing Testssupporting
confidence: 92%